Case Report: Elevated myocardial enzymes in a patient with metastatic rectal cancer without myocardial injury - Zhao, Yalei; Ma, Xiaopeng; Chang, Xiaojing; Li, Mingda; Hao, Yinghao; Zhang, Guojian; Tian, Zhesen (Frontiers in Oncology, 2026)
In clinical practice, myocardial injury is commonly screened using electrocardiograms and high-sensitivity troponin, but tumor patients may present with abnormalities in myocardial enzymes-a routine panel including creatine kinase (CK), CK-MB isoenzyme, lactate dehydrogenase (LDH), hydroxybutyrate dehydrogenase (HBDH), and myoglobin (MYO)-without corresponding ECG or troponin changes. This phenomenon may be related to tumor burden and tumor invasion rather than primary heart disease. Dynamic monitoring of myocardial enzyme abnormalities in patients with metastatic colorectal cancer has not been reported. This case provides a detailed analysis, offering clinical evidence for exploring the relationship between myocardial enzymes and tumor occurrence and development. A 67-year-old male patient with advanced rectal cancer and multiple metastases received chemotherapy with oxaliplatin and capecitabine, targeted therapy with bevacizumab, denosumab for bone metastases, and local radiotherapy. Dynamic monitoring during the treatment showed that the levels of myocardial enzymes significantly increased at the initial stage of metastasis, but there was no evidence of myocardial injury. When the tumor partially responded to the treatment, the expression levels of myocardial enzymes decreased. However, when the condition deteriorated and the number of metastatic lesions increased, the expression levels of myocardial enzymes sharply rose again, eventually accompanying the patient’s death. The non-cardiac injury-related increase in myocardial enzymes is closely associated with tumor burden and cancer activity, and can serve as a dynamic indicator for evaluating the efficacy of radiotherapy and chemotherapy and disease progression.